Recent developments of phosphodiesterase inhibitors: Clinical trials, emerging indications and novel molecules - Bondarev, Andrey D.; Attwood, Misty M.; Jonsson, Jörgen; Chubarev, Vladimir N.; Tarasov, Vadim V.; Liu, Wen; Schiöth, Helgi B. (Frontiers in Pharmacology, 2022)
The phosphodiesterase (PDE) enzymes, key regulator of the cyclic nucleotide signal transduction system, are long-established as attractive therapeutic targets. During investigation of trends within clinical trials, we have identified a particularly high number of clinical trials involving PDE inhibitors, prompting us to further evaluate the current status of this class of therapeutic agents. In total, we have identified 87 agents with PDE-inhibiting capacity, of which 85 interact with PDE enzymes as primary target. We provide an overview of the clinical drug development with focus on the current clinical uses, novel molecules and indications, highlighting relevant clinical studies. We found that the bulk of current clinical uses for this class of therapeutic agents are chronic obstructive pulmonary disease (COPD), vascular and cardiovascular disorders and inflammatory skin conditions. In COPD, particularly, PDE inhibitors are characterised by the compliance-limiting adverse reactions. We discuss efforts directed to appropriately adjusting the dose regimens and conducting structure-activity relationship studies to determine the effect of structural features on safety profile. The ongoing development predominantly concentrates on central nervous system diseases, such as schizophrenia, Alzheimer’s disease, Parkinson’s disease and fragile X syndrome; notable advancements are being also made in mycobacterial infections, HIV and Duchenne muscular dystrophy. Our analysis predicts the diversification of PDE inhibitors' will continue to grow thanks to the molecules in preclinical development and the ongoing research involving drugs in clinical development.